Clinicopathologic Characteristics of Multifocal Gastric Adenocarcinoma - M Kalbasi (Babol University of Medical Sciences, 2019)
BACKGROUNDANDOBJECTIVE: Gastric cancer is the fifth prevalent cancer in worldwide. Among of this, adenocarcinoma is more than 95% of all case and most prevalent. According to gastric adenocarcinoma is resistant to adjuvant therapy, surgical resection is the cardinal strategies of treatment. One of the problems with treating adenocarcinoma of the stomach is that its main causes are malignant or pre-malignant changes in the residual gastric tissue that may be neglected during resection. By recognizing these lesions and resection, they can be expected to reduce the malignancy. Therefore, this study was conducted to investigate the characteristics of non-tumoral gastric tissue in terms of malignant or pre-malignant changes. METHODS: In this retrospective cross-sectional study, 112 patients who had undergone total gastrectomy in the hospitals affiliated to Babol University of Medical Sciences during the period of 2013-2017 were examined and analyzed for age, sex, type and location of tumor. FINDINGS: Of 112 cases that studied,72 cases (64.3%) were male and 40 cases (35.7%) were female. The mean of ages was 64.7±8.6 year. Poorly differentiated pathology in 60.7% and well differentiated pathology in 39.3% of patients were seen. In 64 patients (57%), there was synchronous lesions in addition to primary pathology. These synchronous lesions were related statistically significant to pathology, cancer stage and gender. CONCLUSION: Based on the results of this study, it can be concluded that resection should be accompanied by considering simultaneous lesions in addition to primary pathology, which can be a reason for total gastrectomy as a standard treatment for gastric cancer.